2015
DOI: 10.1155/2015/871759
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Beliefs about Infant-Directed Speech: The Role of Family Dynamics

Abstract: The research investigated the relationship between family dynamics and the beliefs about the benefits of talking to infants. Prior research has shown that language development is enhanced by verbal interaction with others. We tested two hypotheses: (a) men may view talking to infants as less beneficial than women and (b) one's relationships with parents would be related to the extent to which young adults view talking to infants as beneficial. In a study with 301 undergraduates (181 women, 120 men), we confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Concomitantly, these trends may be explained by differing beliefs regarding child language development. For instance, in a survey of 180 female and 120 male undergraduates in the Midwest, Kennison and Byrd-Craven (2015) found that men were significantly less likely to believe that infantdirected speech was beneficial to infants' development. Moreover, significantly more men reported that using "baby talk" had been discouraged in their families.…”
Section: Parental Inputmentioning
confidence: 99%
“…Concomitantly, these trends may be explained by differing beliefs regarding child language development. For instance, in a survey of 180 female and 120 male undergraduates in the Midwest, Kennison and Byrd-Craven (2015) found that men were significantly less likely to believe that infantdirected speech was beneficial to infants' development. Moreover, significantly more men reported that using "baby talk" had been discouraged in their families.…”
Section: Parental Inputmentioning
confidence: 99%
“…The research on the relation between paternal knowledge around language development and paternal language input is virtually nonexistent. One recent survey reported that males were significantly less likely to believe that parentese was beneficial to infants’ development compared to females, but participants were non‐parents (Kennison & Byrd‐Craven, 2015). To our knowledge, no other study to date explores this relation.…”
Section: Introductionmentioning
confidence: 99%
“…One study found that first-time mothers were unsure of the rationale for using parentese with their infants, despite the fact that they seemed to recognize the importance of early language input to children's language learning (Whitmarsh, 2011). Another recent study reports that, compared to females, males were significantly less likely to believe that parentese was beneficial to infant development; however, participants in this study were non-parents (Kennison & Byrd-Craven, 2015).…”
Section: Introductionmentioning
confidence: 63%